Readability levels and prominance of issues in editorial articles of Philippine daily Inquirer and Philippine Star. - de Leon, Kristel Anne
This study aims to know the readability levels of issues in the editorial articles of Philippine Daily Inquirer and Philippine Star. This study also aims to know the prominence of issues in the editorial of both newspapers., The researchers made the study within a span of two weeks with 14 issues for each newspapers for a total of 28 articles. Also, they made use of the Flesch Readability Ease formula and Gunning Fog Index to determine the level of articles' readability. The result for the Flesch Reading Ease Readability Formula was labeled as VERY CONFUSING, DIFFICULT, FAIRLY DIFFICULT, STANDARD, FAIRLY EASY, EASY, or VERY EASY. With the use of Gunning Fog Index, there is a readability grade standard of 12. This is equivalent to the age of Grade 6 students in the Philippines and Junior High School Seniors in American standards. In Gunning Fog Index, an article's readability which exceeds the grade of 12 is considered difficult. The Philippine Daily Inquirer has an editorial with the highest grade of 48.8 for the Flesch Reading Ease Readability which was labeled as DIFFICULT and another editorial with the highest grade of 20.99 for the Gunning Fox Index. The Philippine Star also has the highest readability of 48.9 for the Flesch Reading Ease Readability which we also labeled DIFFICULT and another article has a highest grade of 20.11 for the Gunning Fog Index. Both Philippine Daily Inquirer and Philippine Star editorial articles, therefore, are difficult to read. The researchers were able to determine the prominent issues in editorial articles by doing a frequency count of the issues and determining its placement or the space it occupied in the newspaper. To identify which type of issue the editorials focus on, articles were categorized whether as political, social, economic or religious. While the Philippine Star does not discuss political issues, majority of editorial articles of both newspapers delve on politically-inclined topics. The most prominent issue during the span of the study is the Bangsamoro Juridical Entity and the Memorandum of Agreement between the Philippine government and the MILF.